Intestinal Organoids as a Novel Complementary Model to Dissect Inflammatory Bowel Disease - L. Schulte; M. Hohwieler; M. Müller; J. Klaus (Hindawi Limited, 2019)
Inflammatory bowel diseases (IBDs) include colitis ulcerosa and Crohn's disease, besides the rare microscopic colitis. Both diseases show a long-lasting, relapsing-remitting, or even chronic active course with tremendous impact on quality of life. IBDs frequently cause disability, surgical interventions, and high costs; as in other autoimmune diseases, their prevalent occurrence at an early phase of life raises the burden on health care systems. Unfortunately, our understanding of the pathogenesis is still incomplete and treatment therefore largely focuses on suppressing the resulting excessive inflammation. One obstacle for deciphering the causative processes is the scarcity of models that parallel the development of the disease, since intestinal inflammation is mostly induced artificially; moreover, the intestinal epithelium, which strongly contributes to IBD pathogenesis, is difficult to assess. Recently, the development of intestinal epithelial organoids has overcome many of those problems. Here, we give an overview on the current understanding of the pathogenesis of IBDs with reference to the limitations of previous well-established experimental models. We highlight the advantages and detriments of recent organoid-based experimental setups within the IBD field and suggest possible future applications.